2022
DOI: 10.3390/chemosensors10070252
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymer Functionalized Bi2S3/Ti3C2TX MXene Nanocomposites for Photoelectrochemical/Electrochemical Dual-Mode Sensing of Chlorogenic Acid

Abstract: We report the proof-of-concept of molecularly imprinted polymer (MIP) functionalized Bi2S3/Ti3C2TX MXene nanocomposites for photoelectrochemical (PEC)/electrochemical (EC) dual-mode sensing of chlorogenic acid (CGA). Specifically, the in-situ growth of the Bi2S3/Ti3C2TX MXene served as a transducer substrate for molecularly imprinted polymers such as PEC and EC signal generators, due to its high surface area, suitable bandwidth and abundant active sites. In addition, the chitosan as a binder was encapsulated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 61 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…The research results showed that the dual-mode sensor greatly improves the reliability of the results. 20 DNA nanotechnology greatly contributed to signal amplication in electrochemical analysis. DNA walkers can move autonomously along engineered DNA tracks and have been widely used in the elds of material assembly and biosensors because of their remarkable mobility and continuous synthesis ability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research results showed that the dual-mode sensor greatly improves the reliability of the results. 20 DNA nanotechnology greatly contributed to signal amplication in electrochemical analysis. DNA walkers can move autonomously along engineered DNA tracks and have been widely used in the elds of material assembly and biosensors because of their remarkable mobility and continuous synthesis ability.…”
Section: Introductionmentioning
confidence: 99%
“…The research results showed that the dual-mode sensor greatly improves the reliability of the results. 20 …”
Section: Introductionmentioning
confidence: 99%